Service Performance Analysis and Its Impact on Repurchase Intention in The Indonesian Airline Industry - Suryaneta; Manurung, Aderani Yeusy; Alhakiim, Abiyyu Dzaky; Afrizal, Al Shifa Juni (Program Studi S3 Ilmu Manajemen, 2024)
This study investigates the impact of service quality on repurchase intention in the Indonesian airline industry using the ServPerf framework. The research aims to identify the relationship and influence of five ServPerf indicators - assurance, empathy, reliability, responsiveness, and tangible - on passengers’ intention to repurchase airline services. A quantitative approach was employed, involving a survey of 177 respondents who had used domestic airline services in Indonesia within the past year. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that all five ServPerf indicators significantly affect repurchase intention. However, the results also indicate that Indonesian airlines are not effectively implementing all ServPerf dimensions, leading to customer dissatisfaction and a decrease in repurchase intention. The study highlights the need for Indonesian airlines to prioritize service quality improvements, particularly in the areas of reliability, responsiveness, and tangible aspects. The research suggests that investing in employee training, adopting a customer-centric approach, and continuously monitoring and enhancing service standards are crucial for airlines to remain competitive and foster long-term customer loyalty. The study contributes to the understanding of service quality and repurchase intention in the airline industry and offers valuable insights for airline managers and researchers. Future research directions are proposed, including comparative analyses across different countries, longitudinal studies, the inclusion of additional variables, qualitative research, and industry-specific adaptations of the ServPerf framework.